Breaking down barriers: recommendations for improving sexual abuse reporting rates in British South Asian communities - Harrison, Karen (The British journal of criminology, 2018)
Sexual abuse reporting rates, which are low in general, are thought to be even worse for those living within British South Asian communities. After brief consideration of why British South Asian women and children do not report sexual abuse, this article focuses on the working practices of the non-governmental agencies that support such women. It reflects on existing legislation and policy and makes several key recommendations with reference to how this, along with practice, should change. The findings indicate an urgent need for a national training programme, the implementation of mandatory healthy relationship programmes, enhanced community involvement, outreach work and the creation of victim groups and mentor schemes.